SoMe, So What? : Introduktion - Hedegaard Heiselberg, Maj; Madsen, My; Weisdorf, Matti; Mølholm Kjærulf, Emilie; Boe Hüttel, Astrid; Hastrup Kristensen, Anne Marie; List, Henriette (Tidsskriftet Antropologi, 2026)
SoMe, So What? - Introduktion